CO 2 lasers to destroy defiance of nanobacteria - Jafar Kolahi; Reza Birang (Wolters Kluwer Medknow Publications, 2015)
Introduction: Nanobacteria are mysterious particles that have spurred one of the biggest controversies in modern microbiology. The apatite mineral around the nanobacteria serves as a primary defense shield against various chemicals and extremely harsh condition. It is combined with a very slow metabolism of nanobacteria. These two items would be the likely explanation for the sever resistance of nanobacteria. The Hypothesis: The CO 2 laser is a continuous wave gas laser and emits infrared light at 9,600-10,600 nm in an easily manipulated focused beam that is well absorbed by water and hydroxyapatite. Hence, it seems logical to postulate that CO 2 laser can be used successfully to destroy defensive external hydroxyapatite layer of nanobacteria. Evaluation of the Hypothesis: Main criticism with this hypothesis is differential radiation of nanobacteria. It is well known that CO 2 laser has high water absorption and consequently can cause unwanted damage to human host tissues.